Regional Peculiarities of Bilogical State of Antarctic Krill Euphausia superba Dana in Shelf Waters of the South Georgia in June-August 2004 - Zhuk, N. N.; Savych, V. S. (Ukrainian Antarctic Journal, 2005)
The data collected in the shelf waters of the northern South Georgia allowed determining the morpho-physiological state of Antarctic krill (Euphausia superba) in the winter months of the Southern Hemisphere (June-August, 2004). The analysis of variation curves permit distinguishing three krill size groups: the first group is small krill (of modal size 32-40 mm), the second group consists of comparatively large crustaceans (of modal size 34-44 mm), and the third – large krill (of modal size 44-50 mm). Changeability of their distribution was found: on the north-western shelf small crustaceans prevailed (Group I). As the fishery was moving to the east the rate of juveniles decreased considerably, and the abundance of the second group krill increased. During winter krill groups of the same size had similar morpho-physiological state both on the north-western and north-eastern ground. The differences were recorded in the second half of the winter. They dealt with maturity stages of females and males: in June males and females were at I and II stages, and in July-August – at stages II and II-III, correspondingly. As it was before (2001-2003), among large krill individuals the affection of carapace soft tissues and its chitinous cover was found. The percentage of the affected krill on the north-western ground reached 7.5, and on the north-eastern one – 5.5.